Effects of Neu3 on the dynamics of flotillin 1 dependent endocytosis - Huang, Yongxue. (2009)
Hog cells were transfected with Neu3-EGFP (Enhanced green fluorescent protein), flotillin 1-EGFP or Neu3-HA and flotillin 1-EGFP to test the effect that Neu3 has on the dynamics of flotillin 1 dependent endocytosis. Cells that were transfected with Neu3-HA and flotillin 1-EGFP showed lower lateral average speeds and longer dwell time, implying overall lower average speed compared to those transfected with flotillin 1 only. Also, they showed lower vesicular movement in general as evident from their lower CDLong values over time compared to flotillin 1 transfected cells. They also have a different movement as evident from the different CDLong, CDArea, CDshort and aspect ratio. The average budding rate in cells transfected with Neu3-HA and flotillin 1-EGFP is also slower than cells transfected with flotillin 1 only.